Multimaterial Microrobots for pH Sensing Fabricated Using Sequential 3D and 4D Printing with Automated Alignment - Delaney, Colm (Wiley, 2026)
Microscale pH sensing is important for the study and control of biological and chemical processes. While current tools for microscale pH measurements have their limitations, microrobots are a promising alternative. In this work, the use of multimaterial microrobots for microscale pH sensing is proposed. The microrobots consist of a hard polymer backbone, enabling transportation using optical trapping, and 4D printed smart material sensing elements. A custom automated alignment program is employed to ensure rapid and accurate alignment of the smart material onto the hard polymer backbone. The potential of the microrobots for pH sensing is demonstrated with visual readout from optical microscopy images. The hydrogel sensing elements exhibit a 32 ± 11% size increase from pH 2.3 to 8.8, most of which occurs between ≈pH 5 and ≈pH 7. The swelling performance shows no significant change after repeated cycling from acidic to neutral pH and storage for up to 2 months. When assessing the mobility of the microrobots, speeds of ≈14 μm s−1 can be reached using optical trapping in a phosphate-buffered saline solution. The swelling response, reusability, and high mobility of the microrobots make them promising tools for pH sensing in microfluidic devices.
PUBLISHED